KERAJINAN TANGAN KERTAS KORAN BEKAS DALAM MENGURANGI LIMBAH ANORGANIK DI KELURAHAN MANDALA KECAMATAN MAMAJANG KOTA MAKASSAR - Muhe, Arniati; Arsal, Muryani; Asriadi, Andi Amran (Universitas Muhammadiyah Parepare, 2020)
The Stimulus Community Partnership Program (PKMS) in Mandala Village, Mamajang District, Makassar City, aims to overcome the problem of environmental pollution due to increasing household waste production and the lack of 3R (reuse, reduce, recycle) awareness in the community. Through training in managing inorganic waste into recycling creations, this program aims to convert waste into goods that have economic value and empower the economy of local communities, especially housewives. The program implementation stages include imparting knowledge, conducting training, producing recycled creations, and preparing a final report. Evaluation of the results of program implementation shows success in achieving the number of participants, training objectives, target material, and participant abilities. As a result, this program provides significant benefits for the community, including a new understanding of waste management, increased income, and participation in protecting the environment. In conclusion, PKMS in Mandala Village is a positive step in overcoming environmental and economic problems, showing the importance of collaboration between the government, educational institutions, and the community in creating sustainable solutions.